Fluoroquinolone Resistance in Neisseria gonorrhoeae After Cessation of Ciprofloxacin Usage in San Francisco: Using Molecular Typing to Investigate Strain Turnover. Issue 2 (February 2015) - Espinosa, Kiana; Park, Jason A.; Gerrity, Jillian J.; Buono, Sean; Shearer, Alexandria; Dick, Cindy; Mak, Mae Ling; Teramoto, Kyla; Klausner, Jeffrey D.; Pandori, Mark; Hess, David
Abstract : Background: Ciprofloxacin resistance (CipR) among gonococcal strains in San Francisco (SF) increased between 2001 and 2006 and decreased between 2007 and 2009. Molecular typing of isolates obtained from 2005 to 2009 was performed to elucidate changes in CipR prevalence. Methods: A total of 2526 samples were collected at the SF City Clinic between 2001 and 2009. Minimum inhibitory concentrations to ciprofloxacin were obtained by agar dilution. Prevalences of CipR strains were determined, with corresponding confidence intervals (CIs). Between 2005 and 2009, 460 isolates were selected for molecular typing using Neisseria gonorrhoeae multiantigen sequence typing. Results: Between 2001 and 2006, the prevalence of CipR increased from 3.4% (95% CI, 1.3%–5.4%) to 44% (95% CI, 39%–50%). However, in 2007 prevalence began to decrease, reaching 9.6% (95% CI, 6.0%–13%) by 2009. Of the 203 strain types identified between 2005 and 2009, 126 genogroups of closely related strain types were formed (varying by ⩽1% at both target loci). Levels of CipR within the data set correlate with the prevalence of 3 major genogroups (G): G437, G1407, and G3112. Conclusions: Molecular typing reveals that CipR within the tested population is maintained by strain turnover between resistant genogroups. Despite early recommendation in 2002 to stop ciprofloxacin use in California, CipR in SF increased through 2006. The subsequent decrease in CipR corresponds with the 2007 national recommendation to cease ciprofloxacin treatment of gonorrhea, which suggests that national recommendations are potentially more effective at reducing CipR than regional recommendations in areas with high strain turnover. Abstract : A study of gonorrhea isolates from San Francisco found changes in the prevalence of ciprofloxacin resistance and used molecular typing to observe strain turnover within the population.